Barriers to and Facilitators for Teachers’ Wellbeing - Gearhart, Cassandra A.; Blaydes, Madison; McCarthy, Christopher J. (Frontiers in Psychology, 2022)
Teaching is widely recognized as a stressful profession, which has been connected to burnout and high turnover of qualified teachers. Despite increasing attention on teacher wellbeing, stress management interventions are often underutilized and demonstrate small effect sizes, and research on teachers’ informal stress management practices and desired resources is limited. It is likely that formal and informal intervention effectiveness is limited by teachers’ ability to access existing resources and navigate the complex educational systems they inhabit. The study explored the barriers to and facilitators for teachers’ engagement in formal and informal stress management interventions and desired resources across socioecological levels. Thirty-two teachers participated across four focus groups. Inductive thematic analysis was used to identify relevant themes. Personal barriers (e.g., guilt about self-prioritization), environmental barriers (e.g., mixed messages about self-care), and improved campus resources (e.g., scheduled opportunities to destress) were common themes. Recommendations for supporting teachers’ wellbeing include self-care affirming messages from peers and administrators, campus- and district-level changes to remove logistical barriers to stress management, and increased connectedness among campus community members.